O engajamento acadêmico de estudantes de ensino superior privado - Rodrigues, Camila Cândido (2022)
This study discusses the academic engagement of higher education students. Its purpose was to know the factors that influence the academic engagement of students in private higher education institutions from their own perspective. The theme is important since academic engagement and student permanence in higher education have a close relationship. That is to say, the more the student is engaged, the clearer become his goals, and thus he goes on for his objective, making his education path more meaningful and reducing the possibility of giving up. Furthermore, as the students realize their learning and goals achievements, they become more engaged. The literature review demonstrates that Higher Education Institutions should promote engaging experiences for their students, support them in their difficulties and provide opportunities for meaningful learning. It also points out that the student needs to commit to their academic responsibilities throughout their graduation, and, moreover, that the academic engagement of students involves three dimensions: affective, cognitive and behavioral dimension. As data collection procedure, questionnaires were employed to previously know the profile of the students selected for the sample. Subsequently, 5 students who were attending the first year of undergraduate Psychology at a Higher Education Institution in the city of São Paulo were interviewed. The interviews were analyzed based on the Content Analysis methodology. Therefore, from the students’ perspective it was possible to understand that academic engagement in Higher Education encompasses factors related to the students’ own view of their future career prospects, personal aspirations and affective involvement with their experiences during their academic career and with the academic community. In addition to that, we understood how the construction of the learning process generates a feeling of satisfaction and nourishes the desire to learn more, while it involves the necessity of the student to make choices, exerting effort and active participation in activities